THE EFFECT OF QUALITY OF INTERNAL AUDIT AND EFFECTIVENESS OF INTERNAL CONTROL SYSTEMS ON GOOD CORPORATE GOVERNANCE IN FINANCE COMPANIES - Edwin Theo Mangasih; Margani Pinasti; Icuk Rangga Bawono (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2020)
The purpose of this research is to analyze the effect of quality of internal audit and the effectiveness of internal control system to corporate governance in finance companies. Quality of internal audit was measured by performance, competency and objectivity. The effectiveness of internal control system was measured by control environment, risk assessment, control activities, information and communication and monitoring. The last variable is good corporate governance was measured by corporate governance framework, protection of shareholders, role of stakeholders, transparency of information and roles and responsibilities of the board of commissioners and board of directors. There were 30 finance companies that become a sample in this research. This study used multiple linear regression as the method of analysis. The result of this research indicated that (1) The quality of internal audit has a positive effect on good corporate governance variable and (2) The effectiveness of internal control system has a positive effect on good corporate governance variable. The result of this research gives implication for internal parties must maintain and improve the existence of the quality of internal audit and the effectiveness of internal control system to achieve a more optimal GCG implementation in company operations. The second implication is for government is expected to be more active in monitoring the activities of finance companies, especially in terms of corporate governance.